Genetic variations in the drug metabolizing enzyme, CYP2E1, among various ethnic populations of Pakistan - Sagheer Ahmed (PeerJ, 2020)
Genetic polymorphism in cytochrome P450 (CYP) monooxygenase genes is an important source of interindividual variability of drug response. CYP enzyme activities may change as a result of such polymorphisms which then, may affect drug metabolism. This would result in a change in the severity and frequency of adverse effects in addition to the non-responder phenomenon. CYP2E1, a member of CYP superfamily, affects the metabolism of several clinically important drugs such as halothane, paracetamol, etc. Genetic variation in CYP2E1 is known to cause significant inter-individual differences in drug response and adverse effects. The degree of genetic variation is found to be different in different populations around the world. The frequencies of two important polymorphisms in the CYP2E1*7C, NC_000010.10:g.135340548A>G (rs2070672) and CYP2E1, NC_000010.10:g.135339244G>C (rs3813865), are not known in the Pakistani population. In the present investigation, 636 healthy human volunteers were screened for these two single nucleotide polymorphism. Our results indicate that about 18% (rs2070672) and 28% (rs3813865) of the Pakistani population has a genotype containing at least one low activity allele. A significant interethnic variation in the frequencies of both the polymorphisms was observed. These results suggest that pharmacogenetics screening for low activity genotypes would be a helpful tool for clinicians when they prescribe medications metabolized by CYP2E1, as a significant fraction of the Pakistani population is expected to have a variable response to these drugs.